A Framework for Exploring Trust and Distrust in Natural Resource Management - Emborg, Jens; Daniels, Steven E.; Walker, Gregg B. (Frontiers in Communication, 2020)
How can one simultaneously hold multiple trust judgments—some positive, some negative—and what relevance does this have to natural resource management processes? The paper examines trust through a lens of multiple simultaneous trust judgments, with application to the literature on trust in natural resource management. The conceptual contributions are 1) a clear distinction between trust and distrust, 2) how multiple trust/distrust judgments can co-exist, and 3) how multiple trust judgments can be assigned to individual versus social/institutional scales. A framework for trust/distrust evaluation emerges in the form of a Trust/Distrust Matrix. One dimension of the matrix is the scales to which trust judgments may be assigned and one is the trust/distrust-judgments one makes that can either be calculus-based or identification-based. A set of propositions relevant to natural resource management are derived from the matrix. The fundamental purpose of this article is to bridge theory and practice.